Central African Republic : First and Second Reviews Under the Extended Credit Facility Arrangement and Request for Waivers of Nonobservance of Performance Criteria-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for the Central African Republic. (IMF Staff Country Reports; Country Report ;, 2021)
The Covid-19 pandemic had a substantial impact on C.A.R.'s economy but appears now somewhat contained. The number of positive cases and related deaths has been very limited over the last few months, even though most containment measures have been progressively loosened. Despite some progress since the February 2019 peace agreement, the security situation remains precarious. Despite some delays in voter registration, the first round of the presidential and general elections is still scheduled on December 27.